Scar sarcoidosis: Clinical features and prognostic significance - Marcoval, Joaquim; Iriarte, Adriana; Rocamora, Gemma; Mañá, Juan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Only a few series of patients with scar sarcoidosis (SS) have been reported. Our aim was to analyse the clinical features of SS patients and their relationship to the prognosis of sarcoidosis. Methods: Patients with systemic sarcoidosis with SS diagnosed between 1980-2017 at Bellvitge University Hospital, were enrolled. Their clinical charts were reviewed to collect the following data: age, sex, ethnicity, number of lesions, location of SS, origin of the scar, association with erythema nodosum or other specific cutaneous lesions, radiological stage at diagnosis, chronic systemic sarcoidosis activity. Results: Forty two of 728 patients with systemic sarcoidosis presented SS (31 females and 11 males, mean age 47.71±13.747 years). SS was present at the onset of systemic sarcoidosis in 35/42 cases (83.33%). Twelve patients had simultaneously erythema nodosum. In 14 patients SS was the only specific cutaneous lesion of sarcoidosis. Foreign bodies were observed in 16 of 26 biopsied SS lesions (61.54%). Radiological stage at diagnosis was 0 for 2 patients, I for 22, II for 13, III for 4, and IV for 1. The activity of systemic sarcoidosis persisted for more than 5 years in 16/42 patients with SS (38.1%) vs. 186/686 patients with systemic sarcoidosis (27.11%), However the differences were not significant (p=0.154). Conclusions: SS was observed in 5.77% of our patients with systemic sarcoidosis. It is usually present at the onset of the disease and is an useful sign for suspicion of a diagnosis of sarcoidosis, but it carries no prognostic significance.